2023
DOI: 10.3390/antiox12051052
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A Ameliorates Nephropathy in High-Fat Diet/Streptozotocin-Induced Diabetic Rats: Effects on NF-kB/NLRP3 Axis, Pyroptosis, and Fibrosis

Abstract: Nephropathy is the most prevalent microvascular disorder in diabetes mellitus. Oxidative stress and inflammatory cascade provoked by the persistent hyperglycemic milieu play integral roles in the aggravation of renal injury and fibrosis. We explored the impact of biochanin A (BCA), an isoflavonoid, on the inflammatory response, nod-like receptor protein 3 (NLRP3) inflammasome activation, oxidative stress, and fibrosis in diabetic kidneys. A high-fat-diet/streptozotocin (HFD/STZ)-induced experimental model of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The end products of glycosylation can also activate endothelial cells, which leads to the expression of prothrombotic factors and the initiation of a cascade of coagulation mechanisms and formation of microthrombi [20], which we found in myocardial micro-hemo-vessels on the 56 th day of the experiment. In addition, the end products of glycosylation interact with their cellular receptors, such as RAGE, to promote the production of active oxygen species (AOS) and activation of the nuclear factor-κB (NF-κB) signalling pathway, which lead to endothelial cell death through pyroptosis [21]. Glycosylation end products trigger a chain reaction of activation of pro-inflammatory cytokines, chemokines and adhesion molecules, promoting the migration of inflammatory cells and the continuation of inflammation in the vascular wall [22].…”
Section: Resultsmentioning
confidence: 99%
“…The end products of glycosylation can also activate endothelial cells, which leads to the expression of prothrombotic factors and the initiation of a cascade of coagulation mechanisms and formation of microthrombi [20], which we found in myocardial micro-hemo-vessels on the 56 th day of the experiment. In addition, the end products of glycosylation interact with their cellular receptors, such as RAGE, to promote the production of active oxygen species (AOS) and activation of the nuclear factor-κB (NF-κB) signalling pathway, which lead to endothelial cell death through pyroptosis [21]. Glycosylation end products trigger a chain reaction of activation of pro-inflammatory cytokines, chemokines and adhesion molecules, promoting the migration of inflammatory cells and the continuation of inflammation in the vascular wall [22].…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β1 becomes active when exposed to oxidative stress or inflammatory cytokines and binds to the respective receptors . Activated TGF-β1 modulates the NF-kB pathway and potentiates mesangial cells’ collagen production and proliferation, leading to the deposition of matrix and renal fibrosis. , Considering these facts, we also studied the effect of CPM on renal fibrosis. We found that CPM exposure significantly increased the collagen deposition area, as evidenced by MT staining.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of PAR-2 has been found to enhance autophagy while preventing inflammation and fibrosis [86]. Contrary to expectations, biochanin A mitigates diabetic nephropathy by downregulating the expression of the TGF-β1 and PAR-2 genes [65,81,82].…”
Section: Anti-diabetic Activitymentioning
confidence: 98%
“…The inhibition of PAR-2 has been found to enhance autophagy while preventing inflammation and fibrosis [86]. Contrary to expectations, biochanin A mitigates diabetic nephropathy by downregulating the expression of the TGF-β1 and PAR-2 genes [65,81,82]. Among the numerous health benefits of isoflavones, biochanin A is widely recognized for its anti-inflammatory, antihyperlipidemic, antioxidant, and anticancer attributes by suppressing TGF-β1 and PAR-2 gene expression in kidney tissues of STZ-induced diabetic rats [80][81][82].…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
See 1 more Smart Citation